Estimation of carotinoid, antioxidant, and oxidant statusby biophotonic scanning in healthy and sick persons with risk factorsof atherosclerosis - V. N. Kim; G. V. Krivulina; V. M. Shevelyev; T. Ye. Suslova; O. V. Gruzdeva; R. S. Karpov (Бюллетень сибирской медицины, 2007)
High accuracy of biophotonic scanning in estimation of skin carotinoid score (SCS) and antioxidant status after 8-week period of correction by LifePak, MarineOmega, and Tegreen97 active dietary supplements is proved in 45 healthy persons with cardiovascular risks and in patients with cardiovascular diseases. SCS increased by 42.8% (p = 0.005) and total antioxidant capacity of blood (TAC) increased by 36.4% (p = 0.005) in health people; while in patients SCS increased by 47.4% (p = 0.001) and TAC increased by 30.3% (p = 0.008). The SCS accuracy in estimation of antioxidant status was 87%.